The first three steps of completing the square to solve the quadratic equation x² + 4x - 6 = 0, are
shown below.
Step 1: x2 + 4x = 6
Step 2: x2 + 4x + 4 = 6 + 4
Step 3: (x + 2)2 = 10
What are the next 3 steps?

Respuesta :

Answer:

The next 3 steps are

Step 4: [tex](x+2)=\pm \sqrt{10}[/tex]

Step 5: [tex]x=-2\pm \sqrt{10}[/tex]

Step 6: [tex]x=-2+\sqrt{10}\ or\x=-2-\sqrt{10}[/tex]

Step-by-step explanation:

Given:

Quadratic Equation is

x² + 4x - 6 = 0

To Find:

x = ?

Solution:

Step 1: x2 + 4x = 6

Step 2: x2 + 4x + 4 = 6 + 4

Step 3: (x + 2)2 = 10

Step 4: [tex](x+2)=\pm \sqrt{10}[/tex]

Step 5: [tex]x=-2\pm \sqrt{10}[/tex]

Step 6: [tex]x=-2+\sqrt{10}\ or\x=-2-\sqrt{10}[/tex]

ACCESS MORE